Allostatic Load and Personality: A 4-Year Longitudinal Study. Issue 3 (April 2016) - Stephan, Yannick; Sutin, Angelina R.; Luchetti, Martina; Terracciano, Antonio
ABSTRACT: Objective: Dysregulation across multiple physiological systems, referred to as allostatic load, has pervasive consequences for an individual's health. The present study examined whether allostatic load is associated with personality and personality changes during a 4-year follow-up. Methods: A total of 5200 participants aged from 50 to 99 years (59.5% women, mean [standard deviation] age = 66.91 [8.88] years) from the Health and Retirement Study provided data on cardiovascular, metabolic, and immune markers at baseline and personality both at baseline and at 4 years later. Results: Higher allostatic load was related to higher neuroticism ( β = 0.03, p = .042), lower extraversion ( β = −0.06, p < .001), and lower conscientiousness ( β = −0.06, p < .001) at baseline, and to declines in extraversion ( β = −0.03, p = .007), conscientiousness ( β = −0.04, p < .001), and agreeableness ( β = −0.02, p = .020) over the 4-year period, controlling for demographic covariates. A significant quadratic relation between allostatic load and changes in openness ( β = −0.03, p = .002) suggested that openness declines when individuals exceed a high level of cumulative physiological dysregulation. No association was found with changes in neuroticism. Conclusions: Allostatic load is associated with personality change across adulthood and old age. The findings indicate that physiological dysregulation across multiple systems challenges personality stability and is associated with accelerated personality traits change. Abstract : Supplemental digital content is available in the text.